Designing a Whatsapp VCOP model to support the effectiveness of blended-learning teacher professional learning sciences short courses - Hanekom, Pauline Wilna (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.